Burden of HIV-Related Stigma and Post-Partum Depression: A Cross-Sectional Study of Patients Attending Prevention of Mother-to-Child Transmission Clinic at Kenyatta National Hospital in Nairobi - Yator, Obadia; Mathai, Muthoni; Albert, Tele; Kumar, Manasi (Frontiers in Psychiatry, 2021)
Background: We look at how various HIV-related stigma subtypes, especially internalizing types, interact with postpartum depression (PPD) among women living with HIV. Additionally, we identify key psychosocial risk factors that influence stigma and PPD among women attending Prevention of Mother-to-Child Transmission (PMTCT) clinics. Methods: In this cross-sectional design, 123 women living with HIV were recruited. Participants ages between 18 and 50, who were at least 8 weeks postpartum seeking PMTCT services at Kenyatta National Hospital (KNH), between June and September 2014 participated in the study. HIV/AIDS Stigma Instrument—PLWHA (HASI–P) was used to assesses stigma and Postpartum depression was assessed by Edinburgh Postnatal Depression Scale (EPDS). Bivariate and multivariate regression models were used to determine the individual characteristics associated with the HIV-related stigma Scale. Post survey a few in-depth-interviews were conducted to explore individuals' stigma and depression experiences. Results: The mean age was 31.2 years (SD = 5.2). Fifty-nine (48%) women screened positive for significant depressive symptoms. Post-partum depression was a significant predictor of internalized stigma, enacted, and total stigma (P < 0.05). Older age was associated with less internalized stigma. Living with a partner was associated with more internalized stigma. Having an income above 100 USD per month was protective against stigma. Having good family social support was protective against internalized stigma. A higher educational level was protective against enacted stigma. Being treated for STIs was a risk factor for both enacted and overall stigma. Conclusions: HIV-related stigma needs to be addressed through integrated mental health care programs in PMTCT. Postpartum depression requires comprehensive management to improve short- and long-term outcomes of women living with HIV.